Fenomena Ngopi di Coffee Shop Pada Gen Z - Azzahra, Marsha; Abdurahman, Ade Irfan; Alamsyah, Alamsyah (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study aims to identify, describe and demonstrate the phenomenon of drinking coffee in a coffee shop for Gen Z in Tangerang City and to find out, describe and demonstrate the meaning of Gen Z in Tangerang City for the coffee phenomenon. The research method that will be used by researchers is qualitative research. The research was conducted using a qualitative descriptive research type with a phenomenological approach. Research data sources are divided into 2 (two), namely primary data sources and secondary data sources. data collection methods, namely observation, interviews and documentation. The triangulation used is source triangulation, data collection technique triangulation and time triangulation. Data analysis techniques used are Data Reduction (Reduction), Data Presentation (Display), and Drawing Conclusions and Verification (Conclusion). The results of the study show that there are several reasons why Generation Z engages in coffee activities at coffee shops. The reason for the Z generation to do coffee activities in coffee shops is based on the mind that needs peace and as a motive for entertainment for each individual. In relation to oneself, it is understood that drinking coffee is not just enjoying a cup of coffee, but drinking coffee in a coffee shop also provides a comfortable atmosphere for each individual. In connection with the public seeing how the views of other people towards informants and coffee activity in the coffee shop are also seen as things to establish good social relations and the meaning of coffee in a coffee shop is seen as something fun so that it can raise mood and mood, as well as a medium self-actualization as well as a medium in obtaining prestige values.